The Effectiveness of Cooperative Script Integrated with Matching Cards in Improving Fifth-Grade Expository Writing Skills - Putri Nurhidayati Amelia; Andarini Permata Cahyaningtyas (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study examined the effectiveness of the Cooperative Script instructional model combined with Matching Card media in developing fifth-grade students’ expository writing competence. Employing a quantitative approach with a quasi-experimental non-equivalent control group design, 50 fifth-grade participants were distributed equally between an experimental and a control class of 25 students each. Writing performance was measured through performance-based tests and analyzed using the Shapiro–Wilk normality test, Levene’s homogeneity test, paired-sample t-test, independent-sample t-test, N-Gain score analysis, and Cohen’s d effect size. Results demonstrated a statistically significant enhancement in students’ expository writing performance following application of the Cooperative Script–Matching Card model. The experimental class recorded a superior posttest score, a moderate N-Gain of 61.45%, and a very large effect size relative to the control class. These outcomes suggest that combining Cooperative Script with Matching Card media effectively fosters active engagement, collaborative knowledge construction, and substantive gains in elementary students’ expository writing ability.